Why Aren't Students with Severe Disabilities Being Placed in General Education Classrooms: Examining the Relations Among Classroom Placement, Learner Outcomes, and Other Factors. (March 2020) - Agran, Martin; Jackson, Lewis; Kurth, Jennifer A.; Ryndak, Diane; Burnette, Kristin; Jameson, Matt; Zagona, Alison; Fitzpatrick, Heather; Wehmeyer, Michael
Placement decisions for students with severe disabilities have often been based less on the students' unique learning needs but more on beliefs and presumptions about student learning, entrenched school district policies that restrict program delivery options, and other variables unrelated to student needs. In light of the benefits associated with inclusive practices for students with severe disabilities, this article examines the foregoing factors to better understand how they affect placement decisions and to identify barriers to implementing at a national level more inclusive placements. The article also addresses systems change solutions, and several new federally funded initiatives that could contribute to authentic changes in placement practices.